Utilization of Herbal Ingredients on Vannamei (Litopenaeus vannamei) In Instalasi Budidaya Laut, Tasikmadu Village, Sub-District Watulimo, Trenggalek Regency, East Java, Indonesia - Putri Nurhanida Rizky; Mita Nur Malasari; Atika Marisa Halim; Anna Fauziah (IJOTA (Indonesian Journal of Tropical Aquatic), 2022)
The purpose of this study was to conduct a technical analysis on vannamei (L. vannamei) rearing activities that utilize herbal ingredients including cultivation systems, preparation, fry stocking, feed management, water quality management, harvesting and post-harvesting in Instalasi Budidaya Laut (IBL), Trenggalek, East Java, Indonesia. Data analysis using descriptive analysis. In this study, the pond preparation process included washing tubs, drying for 3 days, liming at a dose of 30 ppm on the walls and bottom of the pond, filling water with a height of 80 cm and stocking with 300 ppm of Organic Fertilizer (POT). Shrimps acclimatized by adding 1 ml of Bionutren. The stocking density is 800 post larvae/m2 with a total stocking of 5,500 individuals. The feed was fermented for 3 days with the addition of Liquid Organic Fertilizer (POC). Feed management uses an acceleration system, which is feeding 24 hours non-stop according to anco control. The results of water quality monitoring obtained are temperature 28◦C – 32◦C, salinity 12 – 28 ppt, DO 3 – 5 mg/l, pH 6.2 – 7.1. Water quality control is carried out by spreading water POC at a dose of 60 ppm and siphoning is carried out every day starting from DOC 17. Herbal ingredients from temulawak and ginger in bionutren products produced FCR 1.3, SGR 10.42%, shrimp tonnage 60 kg/pond, and the survival rate 53.57%.